TRANSFORMING SCIENCE LEARNING WITH DIGITAL-BASED DEEP LEARNING FOR JUNIOR HIGH SCHOOL STUDENTS - Kusrianto, Wiwin; Lasmawan, I Wayan; Suharta, I Gusti Putu; Widiana, I Wayan (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
ABSTRACT This study aims to examine the application of deep learning technology in the learning process at junior high schools (SMP) in Konawe Regency. Deep learning, as a branch of artificial intelligence (AI), has the potential to improve learning effectiveness through personalisation of teaching materials and comprehensive data analysis of student development. The research objects include four junior high schools in Konawe Regency, namely SMPN 1 Unaaha, SMPN 2 Unaaha, SMPN 1 Wonggeduku, and SMPN 2 Wonggeduku. The method used is a case study with a qualitative approach, which includes interviews with teachers and principals as well as direct observation of the implementation of deep learning in the learning process. The results show that although the implementation of deep learning technology is still on a limited scale, its impact on improving the quality of learning including increased student motivation, better understanding of the material, and more precise ability to analyse student development is quite significant. However, the implementation of this technology still faces a number of obstacles, especially related to infrastructure limitations and the need for continuous training for teachers. Therefore, this study recommends increasing infrastructure support and continuous training so that the potential of deep learning can be maximised in the context of secondary education.   ABSTRAK Penelitian ini bertujuan untuk mengkaji penerapan teknologi pembelajaran mendalam (deep learning) dalam proses pembelajaran di Sekolah Menengah Pertama (SMP) di Kabupaten Konawe. Pembelajaran mendalam, sebagai salah satu cabang kecerdasan buatan (AI), berpotensi meningkatkan efektivitas pembelajaran melalui personalisasi materi ajar dan analisis data perkembangan siswa yang komprehensif. Objek penelitian meliputi empat SMP di Kabupaten Konawe, yaitu SMPN 1 Unaaha, SMPN 2 Unaaha, SMPN 1 Wonggeduku, dan SMPN 2 Wonggeduku. Metode yang digunakan adalah studi kasus dengan pendekatan kualitatif, yang meliputi wawancara dengan guru dan kepala sekolah serta observasi langsung terhadap implementasi pembelajaran mendalam dalam proses pembelajaran. Hasil penelitian menunjukkan bahwa meskipun implementasi teknologi pembelajaran mendalam masih dalam skala terbatas, dampaknya terhadap peningkatan kualitas pembelajaran, termasuk peningkatan motivasi siswa, pemahaman materi yang lebih baik, dan kemampuan menganalisis perkembangan siswa yang lebih presisi, cukup signifikan. Namun, implementasi teknologi ini masih menghadapi sejumlah kendala, terutama terkait keterbatasan infrastruktur dan perlunya pelatihan berkelanjutan bagi guru. Oleh karena itu, studi ini merekomendasikan peningkatan dukungan infrastruktur dan pelatihan berkelanjutan agar potensi pembelajaran mendalam dapat dimaksimalkan dalam konteks pendidikan menengah.